2nd Annual ASCOPE Laboratory Test Correlation Programme on CFR Engine (1981) - Bustami Mustafa; E. Jasjfi (Scientific Contributions Oil and Gas, 1982)
ASCOPE Work Programme for 1981 directed the Technical Committee to conduct the 2nd Annual Laboratory Test Correlation Programme for CFR Engines among petroleum laboratories in the ASCOPE member countries. Member countries taking part in this correlation programme are Indonesia with seven laboratories participating, Malaysia with two laboratories, Thailand and the Philippines with two laboratories each. LEMIGAS Laboratory of Indonesia, as coordinator in this correlation programme, provided the samples to be sent to each participating laboratory. After being tested by the participating laboratories, the test results on these samples were to be sent to PPTMGB "LEMIGAS" in Jakarta for processing, including the determination of the standard deviation. Based on these results, conclusions can be drawn about the deviations of laboratory test results and about outliers to be rejected. For proper analysis, the samples for correlation also require physical and chemical test such as specific gravity, RVP, distillation, and TEL content, in the receiving laboratories to take into account any possible changes in the sample properties which have occured during transportation and storage. abaot w bliy Also important to be observed are ambient and engire operating conditions during the men Jnlog lomt correlation tests. The results of this analysis can then be used as a base for diagnosis of the probable causes of deviations, the occurence of outliers and for recommendations of remedial steps to be taken. The method used for testing the samples is the Bracketing Procedure System, while for rounding the values of the numbers found during the tests the ASA rules for rounding are used. The Grubb's rejection criteria with the use of "T" factors are used in evaluating the possible outliers.